Regional patterns and clinical correlates of basal ganglia morphology in non-medicated schizophrenia - Ballmaier, Martina (2008)
Although structural changes of the basal ganglia are widely implicated in schizophrenia, prior findings in chronically medicated patients show that these changes relate to particular antipsychotic treatments. In unmedicated schizophrenia, local alterations in morphological parameters and their relationships with clinical measures remain unknown. Novel surface-based anatomical modelling methods were applied to magnetic resonance imaging data to examine regional changes in the shape and volume of the caudate, the putamen and the nucleus accumbens in 21 patients (19 males/2 females; mean age=30.7±7.3) who were either antipsychotic-naïve or antipsychotic-free for at least 1 year and 21 healthy comparison subjects (19 males/2 females; mean age=31.1±8.2). Clinical relationships of striatal morphology were based on exploratory analyses. Left and right global putamen volumes were significantly smaller in patients than controls; no significant global volume effects were observed for the caudate and the nucleus accumbens. However, surface deformation mapping results showed localized volume changes prominent bilaterally in medial/lateral anterior regions of the caudate, as well as in anterior and midposterior regions of the putamen, pronounced on the medial surface. A significant positive correlation was observed between right anterior putamen surface contractions and affective flattening, a core negative symptom of schizophrenia. The diagnostic effects of local surface deformations mostly pronounced in the associative striatum, as well as the correlation between anterior putamen morphology and affective flattening in unmedicated schizophrenia suggest disease-specific neuroanatomical abnormalities and distinct cortical-striatal dysconnectivity patterns relevant to altered executive control, motor planning, along with abnormalities of emotional processing.